2009
DOI: 10.1177/1941738109347984
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After Anterior Cruciate Ligament Reconstruction: A Meta-Analysis of Autograft Versus Allograft Tissue

Abstract: Background:Clinical outcomes of autograft and allograft anterior cruciate ligament (ACL) reconstructions are mixed, with some reports of excellent to good outcomes and other reports of early graft failure or significant donor site morbidity.Objective:To determine if there is a difference in functional outcomes, failure rates, and stability between autograft and allograft ACL reconstructions.Data Sources:Medline, Cochrane Central Register of Controlled Trials (Evidence Based Medicine Reviews Collection), Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 67 publications
1
43
0
3
Order By: Relevance
“…While no statistically IKDC International Knee Documentation Committee; BPTB Bone-patellar tendon-bone; NA Not available significant differences were found on all the other outcomes between autograft and allograft ACL reconstruction. Although this meta-analysis included 56 studies, none of the eligible studies was a prospective comparative study (allograft versus autograft) [16]. As to the other three systematic reviews and meta-analyses, when those studies involving the irradiated allografts were excluded for analysis, their findings were consistent with the results of our study [14,15,17].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…While no statistically IKDC International Knee Documentation Committee; BPTB Bone-patellar tendon-bone; NA Not available significant differences were found on all the other outcomes between autograft and allograft ACL reconstruction. Although this meta-analysis included 56 studies, none of the eligible studies was a prospective comparative study (allograft versus autograft) [16]. As to the other three systematic reviews and meta-analyses, when those studies involving the irradiated allografts were excluded for analysis, their findings were consistent with the results of our study [14,15,17].…”
Section: Discussionsupporting
confidence: 82%
“…However, the findings of this study were compromised by the selection bias and questionable statistical methods. Another meta-analysis found that patients with allografts reconstruction might have increased joint laxity as measured by the KT-1000 arthrometer [16]. While no statistically IKDC International Knee Documentation Committee; BPTB Bone-patellar tendon-bone; NA Not available significant differences were found on all the other outcomes between autograft and allograft ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second systematic review evaluated only boneepatellar tendonebone grafts, and the outcomes of interest did not include patient-oriented outcomes or instrumented laxity." Foster 17 None NA Tibor 21 Prodromos, Krych "Two meta-analyses comparing autograft and allograft results have been reported, one with inconclusive results and another that had significant methodological limitations." Hu 18 Prodromos, Krych, Carey, Foster, Tibor "The first meta-analysis .…”
Section: Methodsmentioning
confidence: 97%
“…William G Clancy, Jr Devon A. Nelson, Bruce Reider and Rajesh G Narechania (1982) had 50 patients in their study, 88% of their cases the mode of injury was sports especially football, as popular in western world, contrary to our study. [12] Li et al [13] conducted a study on 25 patients with ACL deficiency and treated with arthroscopy, ranging in age from 17-43 years with an average of 25.8 years. There were 17 patients (68%) caused by sports injury, 24% patients caused by accidental falling and 8% patients caused by traffic injury.…”
Section: Discussionmentioning
confidence: 99%